2008
DOI: 10.3133/ofr20081224
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Types in Coastal Louisiana in 2007

Abstract: northern extent of fresh marshes to the southern end of saline (saltwater) marshes on the beaches of the gulf or of coastal bays. Navigation along these transects and to each sampling site was accomplished by using Global Positioning System (GPS) technology and geographic information system (GIS) software operating on a ruggedized laptop, a procedure that was established during the 1997 vegetation survey by Chabreck and Linscombe. As the surveyors reached each sampling station, dominant plant species were list… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…Their distributions based on a coast-wide aerial survey in 2007 (Sasser et al, 2008) are shown in Fig. 1 and Spartina patens for intermediate and brackish marshes; and Spartina alterniflora and Juncus roemerianus for saline marsh, respectively (Sasser et al, 2008;Visser et al, 2003). The biophysical features of these vegetation types used in this study are listed in Table 1.…”
Section: Study Area and Hurricane Isaac (2012)mentioning
confidence: 98%
See 2 more Smart Citations
“…Their distributions based on a coast-wide aerial survey in 2007 (Sasser et al, 2008) are shown in Fig. 1 and Spartina patens for intermediate and brackish marshes; and Spartina alterniflora and Juncus roemerianus for saline marsh, respectively (Sasser et al, 2008;Visser et al, 2003). The biophysical features of these vegetation types used in this study are listed in Table 1.…”
Section: Study Area and Hurricane Isaac (2012)mentioning
confidence: 98%
“…Storm surges could cause salt water intrusion and result in increased estuarine salinity, thus affecting oyster growth and production. The major vegetation types in the estuary are fresh, intermediate, brackish, and saline marshes (Sasser et al, 2008;Visser et al, 2003). Their distributions based on a coast-wide aerial survey in 2007 (Sasser et al, 2008) are shown in Fig.…”
Section: Study Area and Hurricane Isaac (2012)mentioning
confidence: 98%
See 1 more Smart Citation
“…Located in the deltaic plains of the north-central Gulf of Mexico, the study region encompasses estuarine wetlands [49,50] (Figure 1) located in southern Louisiana. These marshes are scoured by hurricanes that push water with elevated salinity into inland marshes where channels, levees, and impoundments impede overland flow, lengthening marsh exposure to elevated salinity surge water and prolonged inundation that promote marsh alteration and deterioration [51,52].…”
Section: Coastal Description and Site Locationsmentioning
confidence: 99%
“…However, three major diversions, Caernarvon, West Point a la Hache, and Naomi, have operated since the early 1990s ( Figure 1 and Table S1), providing an opportunity to assess trends in plant condition and total marsh area before and after diversions began. The vegetation in all three diversions spans the common marsh types in the LCA, including fresh (Panicum hemitomon, Sagittaria lancifolia), intermediate (Leptochloa fusca, Panicum virgatum), brackish (Spartina patens, S. cynosuroides), and saline marshes (Spartina patens, Distichlis spicata) [Sasser et al, 2008]. Invasive species like Chinese tallow (Triadica sebifera) and water hyacinth (Eichornia crassipes) are also common.…”
Section: Introductionmentioning
confidence: 99%